A NOVEL ONE-POT SYNTHESIS OF HOMOCHIRAL (R)-(-) AND (S)-(+)-FE(CO)(ETA(5)-C5H5)(PPH(3))COCH3 - Cook, S; Costello, J; Davies, S; Kruk, H (1994)
Treatment of the salt [Fe(CO)2(η5-C 5H5)(PPh3)]Br with potassium L-mentholate followed by lithium bromide and methyllithium generates, after work-up and crystallisation, homochiral (S)-(+)-[Fe(CO)(η5-C 5H5)(PPh3)COCH3] in ≥ 30% yield.